2017
DOI: 10.3390/en10091373
|View full text |Cite
|
Sign up to set email alerts
|

New Design of a CNG-H2-AIR Mixer for Internal Combustion Engines: An Experimental and Numerical Study

Abstract: Several studies have aimed to convert diesel engines to dual-or tri-fuel engines to improve their fuel economy and reduce the emissions from diesel engine, however, most of these studies do not consider enhancing the homogeneity of fuel mixtures inside the engine and accurately controlling the air fuel ratio. In this study, a new air-fuel mixer was designed, manufactured and tested. The proposed air-gaseous fuel mixer design was conceived to be suitable for mixing air with compressed natural gas (CNG) and a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…This requires solving the other equations for mixture fractions or species mass fraction. Within this simulation, hydrogen and air are assumed to have no reaction with one another [19,20].…”
Section: Mixing Process Without Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires solving the other equations for mixture fractions or species mass fraction. Within this simulation, hydrogen and air are assumed to have no reaction with one another [19,20].…”
Section: Mixing Process Without Reactionmentioning
confidence: 99%
“…There are three boundary conditions considered. The air inlet boundary, the hydrogen inlet boundary and the outlet boundary [19].…”
Section: Boundary Conditionmentioning
confidence: 99%
“…Non-renewable alternative gaseous fuels mainly include fuels based on petroleum gas (consisting mainly of propane and butane)-Liquefied Petroleum Gas (LPG)-fuels based on natural gas whose main component is methane-Compressed Natural Gas (CNG), Liquefied Natural Gas (LNG) as well as fossil coal processing products [152][153][154][155][156].…”
Section: Introductionmentioning
confidence: 99%
“…Their study suggested that when the CR value is 9.6, a 5 or 10% hydrogen ratio can be used to enhance the power performance and emission performance of a diesel engine. Mahmood et al [16] designed and tested a gas mixer (CNG-H2-AIR Mixer) that mixes natural gas, hydrogen, and air. Through simulation calculations, the gas mixer is suitable for mixing air with compressed natural gas (CNG) and a mixture of hydrogen and compressed natural gas (HCNG), and it can provide a mixture with a high uniformity index to accurately control the air to gas fuel ratio at different engine speeds.…”
Section: Introductionmentioning
confidence: 99%